Mycobacterium avium subsp. avium in lymph nodes and diaphragms of pigs from one infected herd in the Czech Republic - Kriz, Petr; Kaevska, Marija; Slana, Iva; Bartejsova, Iva; Pavlik, Ivo (Journal of food protection, 2014)
This study was performed on 40 finished pigs from one herd naturally infected with Mycobacterium avium subsp. avium. The aim was to investigate the presence and amount of M. a. avium in samples of lymph nodes and diaphragm tissues collected during routine postmortem inspection using the triplex quantitative real time PCR (qPCR) method. We collected, in total, 107 samples: various lymph nodes affected by gross tuberculosis (TB)-like lesions from 17 pig carcasses, as well as samples of head and mesenteric lymph nodes from 23 carcasses without TB-like lesions. Samples of diaphragm tissues were collected from all carcasses. M. a. avium was detected in one or more tissue samples collected from half of the slaughtered pigs tested. Samples of diaphragm tissues of three pigs with detected TB-like lesions contained M. a. avium (10(2) to 10(3) cells per g of sample); the organism was not detected in diaphragm tissues from pigs without TB-like lesions. The qPCR method may be useful for quantification of M. a. avium in pigs for the purposes of foodborne risk assessment.
Keywords: Lymph Nodes; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Diaphragm; zvířata; Czech Republic; Mycobacterium avium; tuberkulóza; Česká republika; Swine Diseases; Swine; nemoci prasat; prasata; bránice; Tuberculosis; Animals; bezpečnost potravin; lymfatické uzliny; Food Safety